Fibre-optic IR-spectroscopy for biomedical diagnostics. Issue 2 (2003) - Bindig Bindig, Uwe Uwe; Gersonde Gersonde, Ingo Ingo; Meinke Meinke, Martina Martina; Becker Becker, Yukiyo Yukiyo; Müller Müller, Gerhard Gerhard
Abstract : The use of microscopy is a valuable means of gaining vital information for medical diagnostics. Due to a number of recent technological developments advances have been made in IR microscopy and in particular, rapid detection methods. Microscopic examination methods usually involve sampling followed by a method of sample purification or preparation. The advantages of the IR analytical method are that it is based on a direct, non‒destructive measurement of sample material and that the resulting IR spectra provide extensive and specific information about the sample composition and structure. The course of a disease can lead to either formation or loss of organic compounds in metabolism as well as changes within the biological matrix. Corresponding changes can also be expected in the IR‒signature in view to the grading of alteration. Our preliminary IR microscopic investigations compared diseased and healthy tissue samples individually and basic information was obtained about the tissue specific spectral signature, taking account of biological variance. Human tissue samples taken from the colon were used for these studies. Given the number of endoscopic applications used in minimally invasive medicine, we hope to establish the IR fibre based procedure as an optical biopsy method for tissue diagnostics. The aqueous environment as well as the IR radiation source, signal detection and the flexible wave guide type will be a limiting factor for an IR system. The hygiene requirements are particularly high for a fibre based system to be used for in vivo applications. First experiments were used to check the transmission of the IR microspectroscopic data. Fibre supported measurements were made in ATR and remission. High powered IR laser diodes were tested in subsequent trials for application in biomedicine. First results are presented on the way to an IR-endo-spectroscopic system.